Analysis of Factors Affecting the Quality of Inpatient Medical Records at Royal Prima Hospital Medan 2021 - Trionyta Debora; Adrian; Mangatas Silaen; Sriwahyuni Nasution; Tan Suyono (International Journal of Health and Pharmaceutical (IJHP), 2022)
Efforts to strengthen the health services provided to patients rely heavily on the use of high-quality, complete, accurate, and timely data to inform decision-making at the clinical, facility, and policy levels in hospitals. However, evidence of gaps in the quality of medical records is often found. At RSU Royal Prima Medan there are still some incomplete data such as writing the actions that have been done to the patient. The purpose of this study was to analyze the factors that affect the quality of medical records as part of the initiative to strengthen the health care system. The research was conducted using a survey method with an explanatory research design. The research population was 612 people and as many as 100 samples analyzed were taken by stratified random sampling. The univariate test showed that most of the respondents had filled out medical records completely (78.0%) and on time (72.0%), but there were 41.0% medical records that were inaccurate and did not meet the legal requirements of medical records (59 ,0%). Bivariate analysis with Chi-Square showed that the variables of knowledge (p=0.001), procedures (p=0.006) and supervision (p=0.003) had an effect on the quality of medical records, while equipment had no significant effect. Of the three factors, the most dominant factor influencing the quality of medical records is the knowledge obtained through multiple logistic regression tests with an OR value of 4 times the risk of affecting the quality of medical records. This research is an indication that poor knowledge will affect the quality of medical records so that the Royal Prima Hospital Medan needs to conduct socialization and training to increase the knowledge of health workers (doctors, nurses, medical recorders).